PENDUGAAN VOLUME DAN PROPORSI SORTIMEN KAYU JATI (Tectona grandis L.f.) DI KPH CEPU PERUM PERHUTANI UNIT I JAWA TENGAH - , AGUS FERI KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Estimated volume of wood is one of the important types of information or data to be collected in the forest inventory activities. The data is one of the basic preparation of a plan required to carry out forest management. This study aimed to obtain the equation model estimators volume of teak wood and proporsion of sortimen volume and preparation of the Local Volume Table types of teak specified into sortimen in KPH Cepu. Equation models are used in the preparation of Local Volume Table is a Berkhoutâs model. This equation is used as a simple because it uses only one independent variable is diameter at breast height of tree. Sample used in the preparation of models are 120 samples and 60 samples were used for model validation. acceptance test performed of regression by variance analysis and t test. Model validation using aggregate deviation and the average deviation. Spurr said if good equation has an aggregate deviation of 1 to -1 and the average deviation of up to 10 percent. Equations are obtained to estimate the total volume in KPH Cepu after regression analysis was V = 0.0003 x Dbh 2.252 (m 3 , cm, n=120, r 2 =0.838). Validation test on the equality values obtained of aggregate deviation is 0488 and the value of the average deviation is 11.6 percent. Based on the criteria for acceptance regression testing and model validation, Local volume tables in KPH Cepu can be prepared based on the formula: sortimen volume AI, AII, AIII = volume estimated x sortimen propotion AI, AII,AIII. The determination of the value of the proportion of AI, AII, AIII determined using samples making up the model and model validation are 180 samples. Use of Local Volume Table in KPH Cepu limited by the lowest value of the diameter at breast height and the highest in the sample used. Dbh lowest value used in the preparation of the Local Volume Table is 19 cm and highest diameter at breast height is 80 cm.